IMPLEMENTATION OF THE ONE REGION ONE OFFTAKER POLICY IN THE DEPARTMENT OF FOOD SECURITY, AGRICULTURE AND FISHERIES OF SUKABUMI CITY - Roby Faridudin; Yana FY Basori; Dine Meigawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The title of this research is “One Region One Offtaker Policy Implementation at the Department of Food Security, Agriculture and Fisheries of Sukabumi City. The purpose of this study was to determine the implementation of the one region one offtaker policy at the Department of Food Security, Agriculture and Fisheries, Sukabumi City. The method used is a qualitative method with a phenomenological approach. Data collection techniques include observation, interviews, documentation. The results showed that the implementation of the one region one offtaker policy at the Department of Food Security, Agriculture and Fisheries of Sukabumi City, not yet comprehensive socialization activities in Sukabumi City, the absence of beryer bed facilities (rice drying machines) for offtakers, an increase in the number of offtakers, there are offtakers who do not have offtaker decision letter, there is assistance that will be provided by the Office of Food Security, Agriculture and Fisheries of Sukabumi City to offtakers but so far they have not received the planned assistance. The supporting factor is the encouragement from the government in implementing the one region one offtaker policy. For the inhibiting factors, there are middlemen who are disadvantaged, farmers who do not want to move from the previous middlemen, middlemen who do not want to become offtakers, lack of knowledge of farmers about the one region one offtaker policy.